Effect of clinical decision support systems on emergency medicine physicians' decision-making: A pilot scenario-based simulation study - Assadi, Azadeh; Laussen, Peter C.; Freire, Gabrielle; Ghassemi, Marzyeh; Trbovich, Patricia C. (Frontiers in Pediatrics, 2022)
Background and objectives Children with congenital heart disease (CHD) are predisposed to rapid deterioration in the face of common childhood illnesses. When they present to their local emergency departments (ED) with acute illness, rapid and accurate diagnosis and treatment is crucial to recovery and survival. Previous studies have shown that ED physicians are uncomfortable caring for patients with CHD and there is a lack of actionable guidance to aid in their decision making. To support ED physicians' key decision components (sensemaking, anticipation, and managing complexity) when managing CHD patients, a Clinical Decision Support System (CDSS) was previously designed. This pilot study evaluates the effect of this CDSS on ED physicians' decision making compared to usual care without clinical decision support. Methods In a pilot scenario-based simulation study with repeated measures, ED physicians managed mock CHD patients with and without the CDSS. We compared ED physicians' CHD-specific and general decision-making processes (e.g., recognizing sepsis, starting antibiotics, and managing symptoms) with and without the use of CDSS. The frequency of participants' utterances related to each key decision components of sensemaking, anticipation, and managing complexity were coded and statistically analyzed for significance. Results Across all decision-making components, the CDSS significantly increased ED physicians' frequency of “CHD specific utterances” (Mean = 5.43, 95%CI: 3.7–7.2) compared to the without CDSS condition (Mean = 2.05, 95%CI: 0.3–3.8) whereas there was no significant difference in frequencies of “general utterances” when using CDSS (Mean = 4.62, 95%CI: 3.1–6.1) compared to without CDSS (Mean = 5.14 95%CI: 4.4–5.9). Conclusion A CDSS that integrates key decision-making components (sensemaking, anticipation, and managing complexity) can trigger and enrich communication between clinicians and enhance the clinical management of CHD patients. For patients with complex and subspecialized diseases such as CHD, a well-designed CDSS can become part of a multifaceted solution that includes knowledge translation, broader communication around interpretation of information, and access to additional expertise to support CHD specific decision-making.